Analysis of dry and wet spells under climate change scenarios : a case of the Upper Mun River Basin, Thailand - Thilakarathne, Bandara Mudiyanselage Madusanka Nuwan; Babel, Mukand Singh; Jourdain, Damien; Kawasaki, Akiyuki; Sutat Weesakul; WEM Project; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
The study aims to analyze the dry and wet spells using Standard Precipitation Index (SPI) with climate change in the future. The dry/wet spells were recognized by selecting truncation levels for dry spells and wet spells respectively. The characteristics of dry/wet spells were examined by theory of runs as magnitude and duration. The appropriate timescale for identification of dry and wet spells was selected by examining SPI series for historical records. Further study was conducted using the selected time as three months for the SPI calculation. The most appropriate distribution model for each characteristic was chosen using Akaike Information Criterion (AIC) and Bayesian InformationCriterion (BIC). The return period analysis is conducted for each characteristics of dry/wet spells. The futureprecipitation datawasacquiredusing six Global Climate Models (GCMs). Quantile mapping withempirical quantiles was used in thebias correction of the precipitation data of six climate models. The analysis revealed that there is a tendency of reducing dry spell magnitude and duration in the future. The increase of wet spell magnitude in far future was shown in the results.
A thesis submitted in partial fulfillment of the requirements for thedegree of Master of Engineering inWater Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2014
Keywords: Climatic change -- Mun River Basin (Thailand)